2018
DOI: 10.1002/aocs.12175
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Physicochemical Properties and Oxidative Stability of Kernel Fruit Oil from the Acrocomia totai Palm Tree

Abstract: This study investigated the effects of variations in oil contents and fatty-acid composition, density, viscosity, acid values, saponification values, specific oxidative stability, and antioxidant concentration of Acrocomia totai kernel oil during fruit maturation. Fatty acids were quantified using 1 H nuclear magnetic resonance (NMR) spectroscopy, gas chromatograph-flame-ionization detector (GC-FID), and Fourier transform Raman (FT-Raman) spectroscopy analyses. The results showed that all physicochemical chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
(59 reference statements)
2
8
0
1
Order By: Relevance
“…This shows that the resulted peaks of palm frying oil in this study might indicate the significant Raman spectra characteristics of vegetable oils. Similar pattern of Raman spectrum of palm oil which exhibited the similar significant peaks were also reported in other studies [17,[19][20]. There were also studies which reported some similar patterns of the Raman spectra of animal fats or oils such as desi ghee, pork lard, beef tallow, duck oil and chicken fat [21][22].…”
Section: Resultssupporting
confidence: 81%
“…This shows that the resulted peaks of palm frying oil in this study might indicate the significant Raman spectra characteristics of vegetable oils. Similar pattern of Raman spectrum of palm oil which exhibited the similar significant peaks were also reported in other studies [17,[19][20]. There were also studies which reported some similar patterns of the Raman spectra of animal fats or oils such as desi ghee, pork lard, beef tallow, duck oil and chicken fat [21][22].…”
Section: Resultssupporting
confidence: 81%
“…In Costa Rica, the average oil content of A. aculeata fruit kernels has been found to range from 48.7 to 58.4% on a dry basis (Alfaro-Solís et al 2020;Lieb et al 2019). Kernels from A. totai fruits in the state of Paraná exhibited an average oil content of 58.3% in the final stages of ripening (Souza et al 2018), higher than the value of 47.76% reported by Machado et al (2015) for fruits from the same region and species. A. sclerocarpa displays a value (55.4%) similar to those of A. aculeata and A. totai (Machado et al 2015).…”
Section: Biometric Characteristics Of Oilsmentioning
confidence: 80%
“…A number of post-harvesting (drying and storing conditions for oil quality maintenance) and pre-processing methods (e.g., oil extraction, enzymatic hydrolysis) were explored (Evaristo et al 2016b;Favaro et al 2017;Silva et al 2017). A new study on the effects of maturity stages on kernel oil reported variations in physicochemical characteristics and composition, thus contributing to a better understanding of the ripening process (Souza et al 2018). During this period, further studies on sustainability aspects were published, providing insights on sustainable supply of acrocomia as an alternative source of vegetable oil.…”
Section: A Short History Of Acrocomia Researchmentioning
confidence: 99%
See 2 more Smart Citations